2003
DOI: 10.1038/ng1253
|View full text |Cite|
|
Sign up to set email alerts
|

Dicer is essential for mouse development

Abstract: To address the biological function of RNA interference (RNAi)-related pathways in mammals, we disrupted the gene Dicer1 in mice. Loss of Dicer1 lead to lethality early in development, with Dicer1-null embryos depleted of stem cells. Coupled with our inability to generate viable Dicer1-null embryonic stem (ES) cells, this suggests a role for Dicer, and, by implication, the RNAi machinery, in maintaining the stem cell population during early mouse development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
1,350
4
15

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,762 publications
(1,401 citation statements)
references
References 14 publications
21
1,350
4
15
Order By: Relevance
“…Bantam overexpression in Drosophila resulted in increased cellular proliferation and prevention of apoptosis with resulting overgrowth of wing and eye tissue. More recent analyses of the RNase III enzyme Dicer in mice have shown that inactivation of this gene results in an inability to produce mature miRNAs and in defective cellular differentiation (Bernstein et al, 2003;Kanellopoulou et al, 2005;Muljo et al, 2005;Murchison et al, 2005). As two characteristics of tumor cells are abnormal cell proliferation and defects in differentiation, the potential dysregulation of miRNAs in human cancer has become an intense area of investigation.…”
Section: Mirnas and Cancermentioning
confidence: 99%
“…Bantam overexpression in Drosophila resulted in increased cellular proliferation and prevention of apoptosis with resulting overgrowth of wing and eye tissue. More recent analyses of the RNase III enzyme Dicer in mice have shown that inactivation of this gene results in an inability to produce mature miRNAs and in defective cellular differentiation (Bernstein et al, 2003;Kanellopoulou et al, 2005;Muljo et al, 2005;Murchison et al, 2005). As two characteristics of tumor cells are abnormal cell proliferation and defects in differentiation, the potential dysregulation of miRNAs in human cancer has become an intense area of investigation.…”
Section: Mirnas and Cancermentioning
confidence: 99%
“…It is clear that either endogenous or exogenous small ( 22 bp) dsRNAs initiate a cascade of events that allow enzymes such as Dicer (or RNaseIII or its equivalent, Bernstein et al 2003) to cleave the target mRNA into 22 bp fragments (Hul et al 2000, Ambros 2001, Seitz et al 2003. The annealing reaction between double stranded siRNAs and single stranded target mRNA forms a triplex complex.…”
Section: Amplification Communication and Epigenetic Persistence Of mentioning
confidence: 99%
“…Suppression of miRNA biogenesis, obtained by knocking out Dicer or DCGR8 genes, leads to an early arrest of mouse embryonic development and of in vitro differentiation of ESCs. 11,12 The most abundant miRNAs in ESCs belong to the mouse miR-290 family and to their human counterpart miR-302 family. 13,14 These miRs are mainly involved in cell cycle regulation and in the prevention of the epigenetic silencing of pluripotent factors, like Oct3/4, Sox2, Nanog and Myc.…”
mentioning
confidence: 99%